The identity of a controversial Neotropical turtle hatchling (Reptilia: Testudines: Chelidae) - Cabrera, Mario Roberto (2015)
The purpose of this paper is to set the correct identity of a hatchling chelid turtle, purportedly the southernmost record of Mesoclemmys vanderhaegei (Bour), whose identification has been doubted repeatedly. This specimen is housed at the Zoologisches Museum Hamburg as ZMH R 1025. We determine that the specimen is a hatchling of the Chaco side-necked turtle Acanthochelys pallidipectoris (Freiberg), species previously known from Santa Fe province. Our conclusion is supported by a string of evidence morphological, of pattern and color, and ecology.